2014
DOI: 10.1583/14-4771mr.1
|View full text |Cite
|
Sign up to set email alerts
|

Graft Inflow Stenosis Induced by the Inflatable Ring Fixation Mechanism of the Ovation Stent-Graft System: Hemodynamic and Clinical Implications

Abstract: The advantages of the Ovation device's unique sealing mechanism come at the expense of a median area inflow stenosis of ∼ 60%. This stenosis does not cause a hemodynamically significant pressure drop. Future modification of the graft ring design may be needed in order to reduce this stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…General anaesthesia was induced with propofol 1 mg kg 21 , fentanyl 1-2 mg kg 21 and cis-atracurium to facilitate endotracheal intubation. The patients were intubated, and maintenance of anaesthesia was achieved with propofol infusion and supplemental doses of fentanyl according to patients' needs.…”
Section: Device Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…General anaesthesia was induced with propofol 1 mg kg 21 , fentanyl 1-2 mg kg 21 and cis-atracurium to facilitate endotracheal intubation. The patients were intubated, and maintenance of anaesthesia was achieved with propofol infusion and supplemental doses of fentanyl according to patients' needs.…”
Section: Device Descriptionmentioning
confidence: 99%
“…21 We now perform this technique on a routine basis. Completion angiography was always performed to evaluate good functioning, patency of renal arteries and the absence of endoleaks ( Figure 3).…”
mentioning
confidence: 99%
“…This aortic volume expands externally even though a residual volume occupies the endograft lumen [6,7]. If the neck is heavily and circumferentially calcified, the rings may fail to expand outside and converge toward the center of the endograft, narrowing the aortic lumen.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors who observed 49 consecutive patients (48 men; mean age, 71.2 ± 7.7 years) successfully treated with the Ovation abdominal aortic stent graft at a single center concluded that its unique sealing mechanism comes at the expense of a median area inflow stenosis of ∼60% [6]. Moreover, some authors suggest that the coexistence of stenotic wall regions exposed to a high shear rate and post-stenotic recirculation zones may lead to platelet activation and a predisposition to thrombus formation and thromboembolic complications [7].…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 1 more Smart Citation